ANALYSIS OF TAX SOCIALIZATION AND TAX SANCTIONS IN THE NEW NORMAL ERA ON INDIVIDUAL TAXPAYER COMPLIANCE - Fitria Jayusman, Sri; Munawaroh, Munawaroh; Zuriani Hasibuan, Melisa; Sri Munawaroh, Wilda (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study was conducted to determine and analyze the socialization of taxation and tax sanctions in the new normal era on the compliance of individual taxpayers, Faculty of Economics, UMN AW Medan. This research is expected to help develop the process of tax obligations in the form of socialization of taxation and sanctions, especially in taxation in the new normal era. In this study, researchers used quantitative methods. The data was processed using the statistical software SPSS 23. The tests used in this study were the data quality test, the normality test and the classical assumption test. Data analysis technique using simple linear regression and hypothesis testing using t test and f test. The population in this study were all individual taxpayers of the Faculty of Economics, UMN AW Medan, amounting to 67 people. Sampling was done by convenience sampling method. The results of the study show that simultaneously taxation socialization and tax sanctions have a significant effect on individual taxpayer compliance. Partially, tax sanctions have a positive and significant effect on individual taxpayer compliance, but tax socialization has no effect on individual taxpayer compliance.